Relational Resources and Teachers’ Well-Being: The Moderating Role of Social Support - Nindy Elise; Dedi Muhammad Siddiq; Nico Irawan; Mariam Setapa (Almana : Jurnal Manajemen dan Bisnis, 2026)
School teachers’ psychological well-being plays a crucial role in sustaining the quality of education; however, relational resources within the school workplace remain underexplored in the literature. This study investigates the effects of workplace compassion and empathy on teachers’ psychological well-being, while examining social support as a moderating variable. A cross-sectional survey was conducted among private vocational high school teachers in Cirebon Regency, Indonesia, using a multistage cluster random sampling technique. After data screening, 239 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that workplace compassion, empathy, and social support are positively associated with teachers’ psychological well-being. Furthermore, social support significantly strengthens the relationship between workplace compassion and psychological well-being, whereas its moderating effect on the empathy–well-being relationship is not supported. These findings highlight the importance of fostering compassionate school environments and strengthening social support systems to enhance teachers’ psychological well-being.